The Demand for Punishment to Promote Cooperation Among Like-Minded People - Christoph Bühren; Astrid Dannenberg (Philipps-University Marburg, School of Business and Economics, 2020)
We use an experiment to test the hypothesis that groups consisting of like-minded cooperators are able to cooperate irrespective of punishment and therefore have a lower demand for a costly punishment institution than groups of like-minded free riders, who are unable to cooperate without punishment. We also predict that the difference in the demand for punishment is particularly large when members know about the composition of their group. The experimental results confirm these hypotheses. However, the information about the composition of the group turns out to be even more important than we expected. It helps cooperative groups to avoid wasting resources for an unneeded punishment institution. In uncooperative groups, it helps members to recognize the need for punishment early on and not to follow an uncooperative path that produces a persistently competitive attitude. These findings highlight the role of group composition and information for institution formation and that lessons learned by one group cannot be readily transferred to other groups.
Keywords: C91; H41; D23; C72; 330; Institution formation; public goods game; cooperation; punishment; controlled group formation